Analysis of Hemodynamic Changes After Medial Patellofemoral Ligament Reconstruction - Inoue, Hiroaki; Arai, Yuji; Nakagawa, Shuji; Fujii, Yuta; Kaihara, Kenta; Takahashi, Kenji (Sports Medicine International Open, 2022)
The resumption of blood flow is an important factor in the remodeling process of the graft. The purpose of this study is to evaluate hemodynamic changes after medial patellofemoral ligament (MPFL) reconstruction using magnetic resonance angiography (MRA) as the evaluation of graft remodeling. Eleven knees that underwent anatomical MPFL reconstruction with the semitendinosus tendon were studied. We evaluated the blood flow around the bone tunnel wall in the arterial phase using MRA approximate 3 months and 1 year after surgery. Clinical and radiological evaluations were also analyzed. MRA showed an inflow vessel into the bone tunnel wall from the medial superior genicular artery on the femoral side, and from the articular branch of the descending genicular artery and the medial superior genicular artery on the patellar side. This contrast effect was decreased at 12 months after surgery in all cases. The clinical scores improved from baseline one year postoperatively. We revealed the blood flow to the bone tunnel wall after anatomical MPFL reconstruction is detected by MRA. The blood flow started within 2 or 3 months postoperatively and was sustained for 12 months. This study supported remodeling of the graft continues 3 months after surgery when the conformity of the patellofemoral joint stabilizes.
Keywords: patellar instability; blood supply; imaging; remodeling; graft healing; ligament reconstruction